Going native: Šamaš-Šuma-Ukīn, assyrian king of Babylon - Zaia, Shana (Iraq, 2019)
Šamaš-šuma-ukīn is a unique case in the Neo-Assyrian Empire: he was a member of the Assyrian royal family who was installed as king of Babylonia but never of Assyria. Previous Assyrian rulers who had control over Babylonia were recognized as kings of both polities, but Šamaš-šuma-ukīn's father, Esarhaddon, had decided to split the empire between two of his sons, giving Ashurbanipal kingship over Assyria and Šamaš-šuma-ukīn the throne of Babylonia. As a result, Šamaš-šuma-ukīn is an intriguing case-study for how political, familial, and cultural identities were constructed in texts and interacted with each other as part of royal self-presentation. This paper shows that, despite Šamaš-šuma-ukīn's familial and cultural identity as an Assyrian, he presents himself as a quintessentially Babylonian king to a greater extent than any of his predecessors. To do so successfully, Šamaš-šuma-ukīn uses Babylonian motifs and titles while ignoring the Assyrian tropes his brother Ashurbanipal retains even in his Babylonian royal inscriptions.